2006
DOI: 10.1038/sj.hdy.6800900
|View full text |Cite
|
Sign up to set email alerts
|

Self-fertilization in mosses: a comparison of heterozygote deficiency between species with combined versus separate sexes

Abstract: Self-fertilization is a key difference of adaptive significance between species with combined versus separate sexes. In haploid-dominant species such as mosses and ferns, species with either combined or separate sexes (monoicous and dioicous, respectively) have the potential to self-fertilize (intergametophytic selfing), but being monoicous allows an additional mode of selfing (intragametophytic selfing). We used allozyme electrophoresis to estimate deviations from expected levels of heterozygosity under Hardy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 39 publications
8
48
0
Order By: Relevance
“…Heterozygote deficiency (F IS ) has previously been estimated to be ∼ 0.41 ± 0.11 for dioicous bryophytes (based on five different species, Eppley et al, 2007). We detected higher values in three of the studied populations (0.64, 0.59 and 0.48, respectively), and lower in one population (0.10) ( Table 1).…”
Section: Inbreedingmentioning
confidence: 71%
“…Heterozygote deficiency (F IS ) has previously been estimated to be ∼ 0.41 ± 0.11 for dioicous bryophytes (based on five different species, Eppley et al, 2007). We detected higher values in three of the studied populations (0.64, 0.59 and 0.48, respectively), and lower in one population (0.10) ( Table 1).…”
Section: Inbreedingmentioning
confidence: 71%
“…Quantifying inbreeding in hermaphrodites P Jarne and P David tetraploids (Ronfort et al, 1998) and situations in which both gametophytic and sporophytic selfing may occur, such as in mosses (see Eppley et al, 2007). A strong advantage of this approach is that F is almost systematically estimated in analyses of population genetic structure, based on co-dominant markers, providing an ample source of data.…”
Section: Population Structure Approachmentioning
confidence: 99%
“…It is common in angiosperms, a group with o10% dioecious species (Renner and Ricklefs, 1995), as well as in other plants, such as mosses (Eppley et al, 2007), and in hermaphroditic animals, such as mollusks or trematodes (Jarne and Auld, 2006). It also occurs in fungi.…”
Section: Introductionmentioning
confidence: 99%
“…All sporophytes had karyotypes consistent with mating within a clonal clump [79,81]. Allozyme and microsatellite studies in monoecious mosses find that most sporophytes are homozygous, consistent with frequent gametophytic selfing [82][83][84], although one study of monoecious liverworts found that 5% of sporophytes of Pellia borealis and 25% of sporophytes of Pellia epiphylla were sired by mating between gametophytes [85,86].…”
Section: (D) Monoecious Matingmentioning
confidence: 99%